Moonsinger - Norton, Andre (Baen Pub. ; Distributed by Simon & Schuster, 2006)
In the first of two stories, the Free Traders' ship is forced down on a seemingly uninhabited planet while on a mission for the Thothian priests; and in the second, Krip, a Free Trader, is changed into an animal by the Moon Singer maiden and faces the danger of not being able to return to his human form.